Novel Mycoviruses Discovered from a Metatranscriptomics Survey of the Phytopathogenic Alternaria Fungus - Wenqing Wang; Xianhong Wang; Chunyan Tu; Mengmeng Yang; Jun Xiang; Liping Wang; Ni Hong; Lifeng Zhai; Guoping Wang (Viruses, 2022)
Alternaria fungus can cause notable diseases in cereals, ornamental plants, vegetables, and fruits around the world. To date, an increasing number of mycoviruses have been accurately and successfully identified in this fungus. In this study, we discovered mycoviruses from 78 strains in 6 species of the genus Alternaria, which were collected from 10 pear production areas using high-throughput sequencing technology. Using the total RNA-seq, we detected the RNA-dependent RNA polymerase of 19 potential viruses and the coat protein of two potential viruses. We successfully confirmed these viruses using reverse transcription polymerase chain reaction with RNA as the template. We identified 12 mycoviruses that were positive-sense single-stranded RNA (+ssRNA) viruses, 5 double-strand RNA (dsRNA) viruses, and 4 negative single-stranded RNA (−ssRNA) viruses. In these viruses, five +ssRNA and four −ssRNA viruses were novel mycoviruses classified into diverse the families Botourmiaviridae, Deltaflexivirus, Mymonaviridea, and Discoviridae. We identified a novel −ssRNA mycovirus isolated from an A. tenuissima strain HB-15 as Alternaria tenuissima negative-stranded RNA virus 2 (AtNSRV2). Additionally, we characterized a novel +ssRNA mycovirus isolated from an A. tenuissima strain SC-8 as Alternaria tenuissima deltaflexivirus 1 (AtDFV1). According to phylogenetic and sequence analyses, we determined that AtNSRV2 was related to the viruses of the genus Sclerotimonavirus in the family Mymonaviridae. We also found that AtDFV1 was related to the virus family Deltaflexivirus. This study is the first to use total RNA sequencing to characterize viruses in Alternaria spp. These results expand the number of Alternaria viruses and demonstrate the diversity of these mycoviruses.